Impact of financial structure on economic growth: Example of Serbia, Croatia and Slovenia - Miljana Janković (Anali Ekonomskog fakulteta u Subotici, 2020)
It is well known that the processes of deregulation, globalization and information technology, which began in the 80s and 90s, led to a review of the fundamentals of the financial system and its structure. At that time, international activity is initiated in connection with the improvement of the financial system through the adjustment of the regulatory and institutional framework. The financial structure in its characteristics can be bank-based or market-based, which is largely conditioned by factors such as relevant policies, culture, infrastructure development, key national sectors of the economy. What is always actual is the question of the mutual influence of the financial sector and the real sector, i.e. the relationship between the parameters of the financial structure and financial development, from one side, and economic growth and development, from the other side, to which the unique answer does not exist. In connection with the above, the subject of research in the paper is the analysis of the financial structure in Serbia, Croatia and Slovenia with the main goal of determining the influence of the parameters of the financial structure on economic growth.